Amoksisilin versus Kotrimoksazol untuk Mengobati Pneumonia yang Tidak Parah: Tinjauan Sistematis - Riana Suwarni; Anjar Nuryanto (PT Kalbe Farma Tbk., 2024)
Introduction: Pneumonia is still one of the common causes of death in children under 5 years old in low-middle-income countries. The common cause of pneumonia is bacteria, requiring antibiotics as treatment. This systematic review evaluates the efficacy of amoxicillin and cotrimoxazole in treating pneumonia. Methods: This systematic review used PRISMA rules to analyze Pubmed and Europe PMC articles. The dose, duration, and therapeutic failure of amoxicillin and cotrimoxazole were assessed. Results: A total of 336 articles were selected for title and abstract screening. Four articles met the requirements, and two were selected for systematic review analysis. A total of 20,646 patients were analyzed, 11,633 (56.3%) received amoxicillin and 9,013 (43.7%) received cotrimoxazole. There was no significant difference in treatment failure between amoxicillin and cotrimoxazole. Conclusion: Amoxicillin has the same efficacy as cotrimoxazole for the management of non-severe pneumonia in children under 5 years old.